2021
DOI: 10.2147/opth.s334297
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Same-Day versus Next-Day Implantation of Intracanalicular Dexamethasone for the Control of Postoperative Inflammation and Pain Following Cataract Surgery

Abstract: Purpose: To evaluate the safety and efficacy of a sustained-release intracanalicular dexamethasone insert for postoperative inflammation and pain implanted in a clinical setting preoperatively or on postoperative day 1. Methods: Single-site, retrospective, contralateral eye study of patients undergoing cataract surgery. Included were subjects with a dexamethasone intracanalicular insert implanted in the clinic immediately prior to surgery in one eye (same-day) and on postoperative day 1 (POD1) in the contralat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…[17][18][19][20]25 The tear film is an integral component in corneal epithelial healing; the fewer disturbances it experiences portend potentially easier re-epithelialization for post-CXL eyes. 9,[13][14][15][16][17][18][19][25][26][27][28][29] It is also worthwhile to note that all CXL patients in this study had a bandage contact lens placed at the time of CXL completion. As the ocular surface is a dynamic environment, and factors such as reflex tearing, blinking, tear film quality, and surface characteristics all play a role in topically administered medications, it may be hypothesized that in terms of re-epithelialization and maintenance of the ocular surface milieu, the topical prednisolone may not have completely penetrated to the ocular surface after CXL because of the application of a BCL, whereas the dexamethasone insert was not necessarily impeded in this manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17][18][19][20]25 The tear film is an integral component in corneal epithelial healing; the fewer disturbances it experiences portend potentially easier re-epithelialization for post-CXL eyes. 9,[13][14][15][16][17][18][19][25][26][27][28][29] It is also worthwhile to note that all CXL patients in this study had a bandage contact lens placed at the time of CXL completion. As the ocular surface is a dynamic environment, and factors such as reflex tearing, blinking, tear film quality, and surface characteristics all play a role in topically administered medications, it may be hypothesized that in terms of re-epithelialization and maintenance of the ocular surface milieu, the topical prednisolone may not have completely penetrated to the ocular surface after CXL because of the application of a BCL, whereas the dexamethasone insert was not necessarily impeded in this manner.…”
Section: Discussionmentioning
confidence: 99%
“…This was interesting to the authors in that instillation of drops could potentially disturb the ocular surface and tear film. 9,[13][14][15][16][17][18][19][25][26][27][28][29] However, perhaps the direct application of steroids to the ocular surface allowed for less inflammation/pain compared with intracanalicular steroids. Of interest, in a study by Ibach et al, in patients who had PRK with an intracanalicular dexamethasone insert in one eye and standard steroid drops in the other eye, 70% of patients preferred the dexamethasone insert; there was no difference in postoperative pain control between groups (based on patient responses to a validated questionnaire).…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse event was raised IOP but none of the patients with IOP increases in either arm (dexamethasone insert arm, n ¼ 16; placebo arm, n ¼ 6) were judged by the investigators to be related to treatment [109]. Moreover, this implant can be inserted at first postoperative day -some studies showed that there was no significant difference when comparing implantation during the surgery and 1 day after [110,111]. Also, in Larsen and others' study, patients preferred dexamethasone implant when compared with topical steroid drops after undergoing bilateral refractive lens exchange [112].…”
Section: Management Of Inflammation With the Dropless Cataract Surgerymentioning
confidence: 99%
“…DEX can be administered by optometrists and ophthalmologists, and can be inserted in the outpatient setting. [13][14][15] The timing of DEX administration is flexible with administration being feasible preoperatively, during surgery, or postoperatively without compromising efficacy or safety. 13,15 DEX has been approved by the US Food and Drug Administration for the treatment of ocular inflammation and pain following ophthalmic surgery and also for the treatment of ocular itching associated with allergic conjunctivitis 16 on the basis of results from multiple Phase 3 clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…13,15 DEX has been approved by the US Food and Drug Administration for the treatment of ocular inflammation and pain following ophthalmic surgery and also for the treatment of ocular itching associated with allergic conjunctivitis 16 on the basis of results from multiple Phase 3 clinical trials. [17][18][19] Real-world studies have further demonstrated the role of DEX in the management of postoperative cataract surgery, 13,14 ocular surface disease, 20 refractive surgery, 21,22 minimally invasive glaucoma surgery, 23 and posterior segment surgery. 24 We administered quantitative survey in this study to assess patient and health care provider attitudes toward DEX and its impact on clinical practice.…”
Section: Introductionmentioning
confidence: 99%